GRIT PROFILE OF MUHAMMADIYAH TASIKMALAYA UNIVERSITY STUDENTS - mohamad mohamad (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
Abstract : This research is motivated by the phenomenon of many industrial companies and organizations that recruit prospective employees by providing a minimum GPA score requirement. Students with low grit are less able to survive in doing a large number of course assignments and also feel unable to concentrate following long hours of lectures. High grit makes individuals work hard, have high standards, focus on fulfilling responsibilities. The purpose of this study was to determine the description of grit in students at Muhammadiyah University of Tasikmalaya, based on gender and to plan a program to increase grit in students. This research uses a quantitative approach with descriptive methods. The instrument used is a grit questionnaire from Angela Duckworth's grit grand theory. The data collection technique used a questionnaire in the form of a Likert scale with a total of 24 item statements distributed to 141 respondents. Sampling using random sampling. The results of this study show that in general the grit of students at the Muhammadyah Tasikmalaya University class of 2018 is in the medium category of 25.5% and in the high category of 74.5%. The description of grit based on gender shows the result (Sig.) 0.164 0.05, which means that there is no significant difference between male and female grit (persistence) at the Muhammadiyah University of Tasikmalaya. Keywords: persistence (grit), student, quantitative descriptive